A Geoecological History of Høgtuvbreen: Vegetation succession on the foreland of a retreating glacier in northern Norway - Young, George Edward (The University of Bergen, 2024)
Norway is facing massive glacial ablation, with projections of 98% loss of glacial cover by the close of the 21st century, releasing thousands of square kilometres to the progression of primary succession. Alongside this, rapid climate change is impacting the altitudinal limit of many ecotones questioning whether some alpine species can respond before climbing ecotones trigger local extinctions. Although Arctic regions are disproportionately affected by climate change, most Scandinavian studies of deglaciated terrain succession focus on southern Norway. Here, the geoecological succession of a northern Norwegian glacier foreland is investigated throughout the Late Holocene to present day. Palaeoenvironmental and climatic fluctuations are reconstructed by combining multiproxy sedimentary analyses with palynological analyses; current vegetation succession is mapped for Leirdalsbreen foreland since the Little Ice Age Maximum, 1778 AD, and patterns of postglacial vegetational succession are focused to northern Norway, with particular attention to Picea abies. Palaeoreconstruction establishes the Neoglacial climate to precede a cryospheric response by one century and attributes Empetrum-Vaccinium heath to be the climax vegetation community for Leirdalen throughout the Late Holocene. Lichenometry dates the retreat of Leirdalsbreen to cover one km between 1778 AD and 1928 AD, and two km from 1943 AD to present day. The foreland released formerly has increased vegetation cover to a 31.7% average, whereas the latter has attained an average of 13.2% with only four dwarf shrubs, one herb, and one pteridophyte being absent from this younger terrain. Two categories of succession are concluded for the foreland of Leirdalsbreen: Rapid Airborne Migration (RAM) of all local species except Empetrum-Vaccinium which establishes through Steady Climax Colonisation (SCC). Both are biogeographically promoted by geomorphology but as SCC [here] is a zoochorical community it exhibits slower establishment than RAM. P. abies shows no ...